A CFD study of wet gas metering over-reading model under high pressure. (October 2019) - Jing, Jiaqiang; Yuan, Ying; Du, Shejiao; Yin, Xiaoyun; Yin, Ran
Abstract: The venturi flow meter is increasingly being preferred in multiphase flow measurement because of its shorter upstream and downstream straight sections, less influenced by the flow pattern and relatively small pressure loss. However, when the venturi is used for wet gas measurement, the over-reading phenomenon occurs due to the presence of a small amount of liquid. Many scholars have established over-reading models to correct the measured values of wet gas. Regrettably, the applicability of these over-reading models under actual high pressure operating conditions has not been verified. Therefore, this review focuses on numerical simulation of the flow of wet gas in the venturi tube under high pressure conditions (11MPa/13MPa/15 MPa). The discrete phase model (DPM) and the standard k-ε model was employed in this review. The simulations results reveals the flow characteristics of wet gas in venturi tube, which includes the flow field distributions, droplet concentration distributions and wall pressure profile distributions, and indicates that the over-reading values increases with the increase of Lockhart-Martinelli parameters and gas volume flow rate, but decreases with the increase of pressure. Moreover, the ISO model has the best performance under high pressure conditions. Highlights: Simulating the flow of wet gas in the venturi tube under a broader range of experimental conditions. By analyzing the applicability of over-reading model under high pressure conditions, the ISO model performs best. Discussing the over-reading influence factors, including Lockhart-Martinelli parameters, gas volume flow rate and pressure. Investigating the flow characteristics of wet gas in venturi tube.